Efektivitas ROM (Range of Motion) terhadap Kekuatan Otot pada Pasien Stroke di Rumah Sakit Royal Prima Tahun 2021 - Sry Desnayati Purba; Bagus Sidiq; Ingkai Krisdayanti Purba; Elfride Hutapea; Kristina L Silalahi; Dedek Sucahyo; Dian Dian (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Muscle weakness in stroke patients will affect muscle contraction. Muscle contraction due to reduced blood supply to the brain, thereby blocking the main nerves of the brain and spinal cord . Blockage ofa oxygen and nutrientsto the brain causes serious health problems because it can cause hemiparesis and even death . The occurrence ofa disturbances in the level ofa physical mobilization of patients is often caused by a movement in the form of bed rest. The ofa a weakened muscle condition associated with a lack ofa physical activity usually appear within a few days. Control ofa the brain to regulate muscle movement has decreased function resulting in reduced muscle mass. This studyiaims to determine the effectiveness ofa ROM (range of motion ) on muscle strength in stroke patients at the RoyaliPrima Hospital in Medan. This studyiusedia quasi-experiment with oneigroup pre-posttest. The instrument used is an observation sheet while the Wilcoxon test is used for testing. Prior to ROM training, most ofa the respondents ' strength was on a scale ofa 3 (67.9 %) and minority muscle strength was on a scale of 4 (10.7%). After doing ROM (Range of Motion) exercise there was an increase in muscle strength where the majority muscle strength on a scale ofa 4 was (45.5) and the muscle strength of the minority patient was on a scale ofa 5 (30.0%). There is an Effectiveness ofiROMi (Range of Motion) on Muscle Strength in Stroke Patients at the Royal Prima Hospital Medan in 2021 with p-value of 0.004.Keywords: ROM, Exercises , Muscle Strength